Zróżnicowanie przestrzenne wydatków budżetów powiatów - wyniki analizy strukturalnej - Bal-Domańska, Beata (Spatial diversification of district budget expenditure vs. scope and cost of provided services - results of structural analysis, 2008)
The article presents results of the study on the structure of districts budget expenditure with reference to the share of district’s urban population (an indicator of demographic urbanization). The objective of carried out analysis was to identify spatial diversification of districts budget expenditure in order to measure the significance of differences as well as their relation to the scope and cost of provided services. Structural approach was applied in the study. The results were based on the measures of complex structures and econometric analysis of models for panel data incorporating due estimation techniques.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (20); 2008; nr 1195, s. 139-149